Myosins in Osteoclast Formation and Function - Beth S. Lee (Biomolecules, 2018)
Skeletal quantity and quality are determined by processes of bone modeling and remodeling, which are undertaken by cells that build and resorb bone as they respond to mechanical, hormonal, and other external and internal signals. As the sole bone resorptive cell type, osteoclasts possess a remarkably dynamic actin cytoskeleton that drives their function in this enterprise. Actin rearrangements guide osteoclasts’ capacity for precursor fusion during differentiation, for migration across bone surfaces and sensing of their composition, and for generation of unique actin superstructures required for the resorptive process. In this regard, it is not surprising that myosins, the superfamily of actin-based motor proteins, play key roles in osteoclast physiology. This review briefly summarizes current knowledge of the osteoclast actin cytoskeleton and describes myosins’ roles in osteoclast differentiation, migration, and actin superstructure patterning.